Answer:
Y=X+(X-3)
Explanation:
I did this exercise by looking at the table
From the numbers given. you can realize that to reach the Y every X number sums a quantity(ex 7+4=11/8+5=13/9+6=15)
if you create the equation Y=X+(X-3)---> then all the numbers in the box are correct. Its all a matter of trying until you realize is correct
EXAMPLESS
Y=X+(X-3)
11=7+(7-3)= CORRECT 11
13=8+(8-3)= CORRECT 13
15=9+(9-3)= CORRECT 15
17=10+(10-3)= CORRECT 17
when you do this you know the equation its ok and reflect the behaviour of the function.